The Impact of the Covid-19 Pandemic on the Performance of Batik, Milk and Culinary MSMEs in the City of Semarang - Mohamad Hasanudin; Marliyati; Ch Retno Gayatri; Sulistyo; Ardian Widiarto (International Journal of Integrative Sciences, 2024)
The most pronounced impact of the COVID-19 pandemic for Milkfish, Culinary, and Batik MSME entrepreneurs are experiencing a decline in sales turnover. After the pandemic subsided, consumer demand began to increase so MSME sales turnover increased. This research uses analysis of each variable using a questionnaire. The results of the survey that has been carried out show that batik MSMEs have the main obstacles in the form of capital and low consumer demand for batik. For milkfish and culinary MSMEs, the problem is low demand from consumers, some milkfish and culinary MSMEs do not yet sell online. The obstacle after the pandemic subsides is the still high price of raw materials. During the COVID-19 pandemic, sales of batik, milkfish, and culinary MSMEs generally experienced a decline in sales turnover of around 40-80%. The employment rate for batik, milkfish, and culinary MSMEs during the COVID-19 period was 15%. MSMEs experienced a reduction in the number of workers and also a reduction in the number of working hours. Milkfish and culinary MSMEs during the COVID-19 pandemic and after the COVID-19 period experienced problems in the raw material supply chain and price increases